2017
DOI: 10.1172/jci.insight.95367
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal IgG in MGUS and multiple myeloma targets infectious pathogens

Abstract: International audienceSubsets of mature B cell neoplasms are linked to infection with intracellular pathogens such as Epstein-Barr virus (EBV), hepatitis C virus (HCV), or Helicobacter pylori. However, the association between infection and the immunoglobulin-secreting (Ig-secreting) B proliferative disorders remains largely unresolved. We investigated whether the monoclonal IgG (mc IgG) produced by patients diagnosed with monoclonal gammopathy of undetermined significance (MGUS) or multiple myeloma (MM) target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 50 publications
(57 reference statements)
4
60
0
Order By: Relevance
“…Therefore, the prevention and treatment of the virus in newly diagnosed patients with MM is essential. If an underlying chronic infection is cleared up early enough in disease progression, it could offer the possibility of preventing MGUS transition to SM and MM in the first place [20]. In addition, we agree with the point that newly diagnosed patients with MM should be screened for serum hepatitis B viral markers universally in HBV endemic areas [22].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Therefore, the prevention and treatment of the virus in newly diagnosed patients with MM is essential. If an underlying chronic infection is cleared up early enough in disease progression, it could offer the possibility of preventing MGUS transition to SM and MM in the first place [20]. In addition, we agree with the point that newly diagnosed patients with MM should be screened for serum hepatitis B viral markers universally in HBV endemic areas [22].…”
Section: Discussionsupporting
confidence: 57%
“…Through molecular analysis, a recent study [19] displayed significant EBV DNA in malignant plasma cell disorders, especially in MM and MGUS patients. Bosseboeuf et al [20] demonstrated that EBV was the most frequent target of purified monoclonal IgG produced by patients with MGUS or MM. They considered that chronic stimulation by infectious Ag may promote MGUS and MM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, the chronically stimulated lineage is at the origin of an increased risk of genetic alteration leading to clonality and malignant transformation. To support this pathogenic process in MGUS and myeloma, we recently reported that six infectious pathogens, including carcinogenic viruses [EBV, HCV, Herpes simplex virus (HSV)] and bacteria ( H. pylori ), are the targets of ~23% of purified mc IgG from MGUS, SM, and MM patients ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Bosseboeuf et al reported that some infectious agents, including H. pylori , may be the target of monoclonal IgG in patients with monoclonal gammopathy of undetermined significance and multiple myeloma, possibly explaining the onset or progression of this hematologic condition …”
Section: Hematologic Diseasesmentioning
confidence: 99%